Building a safe generation: the collaborative role of schools and families in child safety: The Collaborative Role of Schools and Families in Child Safety - Julaikah, Julaikah; Rofiatun, Rofiatun; Tursilowati, Sri Yuni; Rahmah, Hani Auliya; Mahfuzah, Mahfuzah (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Accidents among school-aged children, often linked to unsafe behavior, are a persistent issue. Safety knowledge among children, influenced by parents and teachers, plays a vital role in reducing these risks. This study explores the collaborative roles of parents and teachers in shaping children’s safety behavior and addressing gaps in preventive strategies. Method: The study was conducted in 2024 at Krajan Elementary School and Muhammadiyah Gunturgeni Elementary School in Srandakan, Bantul, using a mixed-methods approach with a convergent parallel design. Participants included 120 respondents (15 teachers and 105 parents) and 105 students. Data were collected through questionnaires, focus group discussions (FGDs), in-depth interviews, and observations using a safe behavior checklist. Results: Findings indicate that 86% of teachers and 88% of parents possess good safety knowledge. However, unsafe behavior persists, with 75% of students displaying unsafe practices during classroom activities. Teachers primarily act as educators and role models, while parents serve as facilitators and motivators. Collaboration between parents and teachers remains reactive, focusing on incident management rather than prevention. Conclusion: The study underscores the need for stronger collaboration between parents and teachers to promote preventive safety measures. By aligning safety practices at school and home through effective communication and shared responsibility, a safer environment can be established for children, fostering lifelong safety behaviors and reducing accident risks.